(untitled) (AYUSHDHARA, 2025)
Fibromyalgia is characterized by persistent, widespread musculoskeletal pain, exhaustion, cognitive disruption, mental disorders, and a variety of somatic symptoms. Fibromyalgia affects more women than men, with a frequency of 2.8% in India. It has a possible Ayurvedic correlation with Gat Vata (Mamsagat Vata). A female patient comes to OPD with complaints of pain at the bilateral thigh region and at the bilateral forearm (myalgia) (VAS-07), pain at the origin of the supraspinatus muscle bilaterally (VAS-04) and the upper quadrant of the buttocks bilaterally (VAS-04), pain at the bilateral calf region (VAS-07), and pain at the bilateral scapular region (VAS-07) with morning stiffness (up to 30 min.) all over the body. Due to the above complaints, she had difficulty doing day-to-day work, along with a disturbed sleeping pattern (4-5 hrs.) and stress from her job. No history of DM, HTN, or IHD. The Chikitsa Siddhant of Mamsagat Vata is Virechana, Niruha Basti. Followed by Shaman Chikitsa, by considering Chikitsa Siddhant, the patient was managed with Deepan, Pachana, followed by Koshtashodhana, Niruha Basti, and Shaman Chikitsa like Dashmool Kashaya, Yogaraj Guggulu, and a combination of Ashwagandha Churna, Chopchini Churna, Pipalimool Churna, Navajeevan Ras, and Mamsyadi Kwath. It shows a significant reduction in pain at the above-mentioned site and an improvement in the quality of life of the patient, which is assessed by the Fibromyalgia Impact Questionnaire before treatment (score: 39/100) and after the treatment (score: 25.5/100). This case study demonstrated the effectiveness of Ayurvedic intervention in the treatment of fibromyalgia.